Picoperovskites: The Smallest Conceivable Isolated Halide Perovskite Structures Formed within Carbon Nanotubes. Issue 10 (25th January 2023) - Kashtiban, Reza J.; Patrick, Christopher E.; Ramasse, Quentin; Walton, Richard I.; Sloan, Jeremy
Abstract: Halide perovskite structures are revolutionizing the design of optoelectronic materials, including solar cells, light‐emitting diodes, and photovoltaics when formed at the quantum scale. Four isolated sub‐nanometer, or picoscale, halide perovskite structures formed inside ≈1.2–1.6 nm single‐walled carbon nanotubes (SWCNTs) by melt insertion from CsPbBr3 and lead‐free CsSnI3 are reported. Three directly relate to the ABX3 perovskite archetype while a fourth is a perovskite‐like lamellar structure with alternating Cs4 and polyhedral Sn4 I x layers. In ≈1.4 nm‐diameter SWCNTs, CsPbBr3 forms Cs3 Pb II Br5 nanowires, one ABX3 unit cell in cross section with the Pb 2+ oxidation state maintained by ordered Cs + vacancies. Within ≈1.2 nm‐diameter SWCNTs, CsPbBr3 and CsSnI3 form inorganic‐polymer‐like bilayer structures, one‐fourth of an ABX3 unit cell in cross section with systematically reproduced ABX3 stoichiometry. Producing these smallest halide perovskite structures at their absolute synthetic cross‐sectional limit enables quantum confinement effects with first‐principles calculations demonstrating bandgap widening compared to corresponding bulk structural forms. Abstract : Halide perovskites CsPbBr3 and lead‐free CsSnI3 form "picoperovskites" in 1.2–1.6 nm‐diameter single‐walled carbon nanotubes with cross‐sectional unit‐cell or sub‐unit‐cell dimensions. The smallest of these are bilayer inorganic polymers retaining ABX3 stoichiometry while intermediate‐scale Cs3 PbBr3 preserves Pb 2+ by forming ordered vacancies. The largest Cs4 Sn4 I x form alternates Cs4 and Sn4 I x layers along the nanotube cavities.